Realisasi Makna Eksperiensial dalam Teks The Sea Eagle: Analisis Sistem Transitivitas - Umar Yais (Bajang Institute, 2026)
This study examines how experiential meaning is constructed in The Sea Eagle through the transitivity system of Systemic Functional Linguistics. It aims to identify the process types and interpret how their distribution contributes to its descriptive character. The study employed a descriptive qualitative design and treated the text as a single documentary source. Clause segmentation and functional classification followed Halliday and Matthiessen’s transitivity framework and Eggins’s clause-based analytical procedure. The calculation comprised finite clauses that could be classified. One ambiguous construction was excluded because its clause boundary could not be established without reconstruction, while two nonfinite material extensions were discussed but omitted from the percentage calculation. Thirteen finite clauses were retained. Relational processes occurred eight times (61.5%), material processes four times (30.8%), and verbal processes once (7.7%). No mental, behavioral, or existential processes were identified. The relational clauses were evenly divided between possessive attributive and intensive attributive patterns, enabling the text to represent the eagle through its physical attributes, possessions, and functional characteristics. Material processes added habitual actions, particularly hunting and walking, whereas the single verbal process introduced an explanatory relation through means. These choices support the text’s descriptive purpose and also suggest a limited affinity with descriptive reports because several statements refer to eagles generically. Since the analysis concerns one text containing grammatical irregularities, the findings describe this specific textual configuration and should not be generalized to descriptive texts or learner writing more broadly.